2019
DOI: 10.1891/1541-6577.33.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators, Barriers, and Outcomes of Self-Initiated HIV Testing: An Integrative Literature Review

Abstract: Background and PurposeHIV testing is an essential tool for identifying people at risk for HIV infection and linking those who are infected to care. Despite the recommendation for routine HIV testing for people who are vulnerable to HIV infection, healthcare professionals experience difficulties initiating discussions related to sexual health and recommending HIV testing. Healthcare professionals not offering HIV testing is a frequently reported reason for delays in testing. Self-initiated HIV testing is unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…14,[23][24][25] Further, there is evidence suggesting this method can increase HIV testing uptake and early diagnosis. [26][27][28][29][30][31][32][33] HIVST is particularly relevant for stigmatized populations as it provides individuals with increased privacy and greater control over their testing needs. 34 The option to test privately at times and locations of choice creates the opportunity to reduce stigma, a significant barrier for MSM, [35][36][37][38][39] BMSM, 36,[39][40][41][42] sex workers, 43,44 prisoners, 45,46 and transgender women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[23][24][25] Further, there is evidence suggesting this method can increase HIV testing uptake and early diagnosis. [26][27][28][29][30][31][32][33] HIVST is particularly relevant for stigmatized populations as it provides individuals with increased privacy and greater control over their testing needs. 34 The option to test privately at times and locations of choice creates the opportunity to reduce stigma, a significant barrier for MSM, [35][36][37][38][39] BMSM, 36,[39][40][41][42] sex workers, 43,44 prisoners, 45,46 and transgender women.…”
Section: Introductionmentioning
confidence: 99%
“…50 Several systematic or literature reviews discuss conditions for HIVST use among key populations, including one demonstrating that individuals who self-initiate HIVST are those having perception of risk for HIV and knowledge about HIV testing availability. 27 A recent literature review found high rates of acceptability of HIVST among MSM but notes that values and preferences of other key populations remain understudied. 51 There are some concerns that HIVST is sub-optimal compared to testing in clinical settings, both in terms of test sensitivity when comparing oral versus blood-based results and options for linkage to care.…”
Section: Introductionmentioning
confidence: 99%
“…To increase HIV testing uptake among young adults, it is crucial to identify and promote alternative strategies for encouraging testing. An exploration of self-initiated HIV testing, that is, testing that is initiated and completed by an individual without an immediate clinician recommendation, could provide vital information for future strategies aimed at improving the uptake of HIV testing among young adults (Adebayo & Salerno, 2019;Joore, Geerlings, Brinkman, van Bergen, & Prins, 2017;Ma, Malcolm, Diaz-Albertini, & Klinoff, 2016). Self-initiated HIV testing includes behaviors such as requesting HIV tests from locations that offer testing or the use of self-testing kits; however, these are not typical testing behaviors among young adults (Adebayo & Salerno, 2019;Joore et al, 2017;Pai et al, 2013).…”
mentioning
confidence: 99%
“…An exploration of self-initiated HIV testing, that is, testing that is initiated and completed by an individual without an immediate clinician recommendation, could provide vital information for future strategies aimed at improving the uptake of HIV testing among young adults (Adebayo & Salerno, 2019;Joore, Geerlings, Brinkman, van Bergen, & Prins, 2017;Ma, Malcolm, Diaz-Albertini, & Klinoff, 2016). Self-initiated HIV testing includes behaviors such as requesting HIV tests from locations that offer testing or the use of self-testing kits; however, these are not typical testing behaviors among young adults (Adebayo & Salerno, 2019;Joore et al, 2017;Pai et al, 2013). Previous studies have found associations between self-initiated HIV testing and increased likelihood of future HIV tests, increased engagement in sexual risk reduction, and improved sexual health outcomes (Adebayo & Salerno, 2019;Joore et al, 2017;Ma et al, 2016;Pai et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation